THE MANAGEMENT OF STUDENTS' CHARACTER DEVELOPMENT ON PESANTREN-BASED SCHOOL IN SMK KY AGENG GIRI DEMAK - Nurwahid, Ahmed Yogie; Fakhruddin, Fakhruddin; Rifai Rc, Achmad (Educational Management, 2020)
Character education in pesantren-based school is an integrated system in building students? character in the school. This character education contains tradition of pesantren applied. School management will be able to run if the principal and the teacher cooperate with each other. The aims of this study are to analyze the planning of students? character development on pesantren-based school in SMK Ky Ageng Giri Demak, to analyze the organization of students? character development on pesantren-based school in SMK Ky Ageng Giri Demak, to analyze the implementation of students? character development on pesantren-based school in SMK Ky Ageng Giri Demak, and to analyze the supervision of students? character development on pesantren-based school in SMK Ky Ageng Giri Demak. The method used in this study was a qualitative description method. The focuses of this study were planning, organizing, implementing and supervising in SMK Ky Ageng Giri Demak. The Sources of data in this study were informants, processes, and documents. Data collection techniques were done by observation conducted at SMK Ky Ageng Giri Demak and interview conducted directly with the informants. The data validity technique used in this study was triangulation. While, the data analysis technique used was description analysis technique. The results of this study that were found by the researchers at SMK Ky Ageng Giri Demak as follow: first was the planning started from polling until determined the program through plenary meeting. Second, organizing was done by using a delegation system. Third, implementing was carried out by the person in charge with the help of the relevant teacher and it was done through intra, extracurricular, and pesentren programs. The last was supervising which was carried out by the principal using interpersonal communication so that the reports would be obtained fully.